Effect of hippotherapy on gait symmetry in children with cerebral palsy: A pilot study. (24th March 2019) - Mutoh, Tomoko; Mutoh, Tatsushi; Tsubone, Hirokazu; Takada, Makoto; Doumura, Misato; Ihara, Masayo; Shimomura, Hideo; Taki, Yasuyuki; Ihara, Masahiro
Summary: We aimed to investigate the effect of hippotherapy on gait symmetry in children with cerebral palsy (CP). Twelve children with Gross Motor Function Classification System (GMFCS) levels II−IV received weekly hippotherapy lesson for 1 year. Gait analyses were performed during a 5‐m walking test, using a portable, tri‐axial accelerometer‐based motion recorder. The baseline symmetry index derived from the Lissajous index (LI) figure before hippotherapy was greater than the LI in age‐matched normal subjects ( P < 0.01). Hippotherapy was associated with a decreased LI (−10.4 ± 4.9%, P = 0.018) and an improved GMFCS score (−0.6 ± 0.7, P = 0.02). These data suggest that hippotherapy has a beneficial effect on symmetry of the trunk movement in children with CP.